Metaphorical expressions for successful doctoral study abroad - Usman, Jarjani; Zainuddin, Zamzami; Lugendo, Dorine; Maskur, Maskur; Murni, Murni (Englisia: Journal of Language, Education, and Humanities, 2023)
Timely positive feedback to students pursuing a Ph.D. program motivates completion.  Drawing upon Skinner's Reinforcement theory and Lakoff and Johnson's Conceptual Metaphor Theory (CMT), this study aimed at uncovering metaphors employed in feedback practices by exploring the linguistic expressions of supervisors and peers, which encouraged students to complete their Ph.D. studies in Australia. The methodology employed the use of a semi-structured interview to delve into the lived experiences of two Indonesian Ph.D. students (currently EFL lecturers) during their studies in Australia. The results that the use of positive expressions from supervisors and peers strongly motivated the students to complete their Ph.D. programs. The four types of expressions used served to praise, give hope, give direction as feedback to support completion, and reminders to keep the student on track. The following expressions were commonly used to motivate completion: "Do not worry, mate, you will get there," and "Wow, it's great work! I understand it is not easy to write academically in such good English, but you did." These expressions metaphorically imply that:  "PhD study is a journey," and "Work speaks louder than words." These findings suggest that positive verbal feedback from supervisors' and peers' can motivate PhD students' completion.